Genomic characterization of a large panel of patient-derived hepatocellular carcinoma xenograft tumor models for preclinical development - Gu, Qingyang (Oncotarget, 2015)
Lack of clinically relevant tumor models dramatically hampers development of effective therapies for hepatocellular carcinoma (HCC). Establishment of patient-derived xenograft (PDX) models that faithfully recapitulate the genetic and phenotypic features of HCC becomes important. In this study, we first established a cohort of 65 stable PDX models of HCC from corresponding Chinese patients. Then we showed that the histology and gene expression patterns of PDX models were highly consistent between xenografts and case-matched original tumors. Genetic alterations, including mutations and DNA copy number alterations (CNAs), of the xenografts correlated well with the published data of HCC patient specimens. Furthermore, differential responses to sorafenib, the standard-of-care agent, in randomly chosen xenografts were unveiled. Finally, in the models expressing high levels of FGFR1 gene according to the genomic data, FGFR1 inhibitor lenvatinib showed greater efficacy than sorafenib. Taken together, our data indicate that PDX models resemble histopathological and genomic characteristics of clinical HCC tumors, as well as recapitulate the differential responses of HCC patients to the standard-of-care treatment. Overall, this large collection of PDX models becomes a clinically relevant platform for drug screening, biomarker discovery and translational research in preclinical setting.